2012
DOI: 10.1177/1098612x12447729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sedation on echocardiographic variables of left atrial and left ventricular function in healthy cats

Abstract: Although sedation is frequently used to facilitate patient compliance in feline echocardiography, the effects of sedative drugs on echocardiographic variables have been poorly documented. This study investigated the effects of two sedation protocols on echocardiographic indices in healthy cats, with special emphasis on the assessment of left atrial size and function, as well as left ventricular diastolic performance. Seven cats underwent echocardiography (transthoracic two-dimensional, spectral Doppler, color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
3
42
1
2
Order By: Relevance
“…Even though acepromazine has a relatively higher IC 50 for hERG channel inhibition, if it used in combination with drugs with potential of prolongation of QT intervals through the hERG channel inhibition, such as sedatives and anesthetics, it might be dangerous to human and animals through a synergistic drug interaction. This interpretation could be support by the reports that acepromazine significantly increased heart rate and blood pressure when it combined with halothane, ketamine, and butorphanol [4445]. These synergistic effects of hERG channel inhibition through the drug interaction could be another explanation of acepromazine possibly inducing long QT syndrome even at higher IC 50 in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Even though acepromazine has a relatively higher IC 50 for hERG channel inhibition, if it used in combination with drugs with potential of prolongation of QT intervals through the hERG channel inhibition, such as sedatives and anesthetics, it might be dangerous to human and animals through a synergistic drug interaction. This interpretation could be support by the reports that acepromazine significantly increased heart rate and blood pressure when it combined with halothane, ketamine, and butorphanol [4445]. These synergistic effects of hERG channel inhibition through the drug interaction could be another explanation of acepromazine possibly inducing long QT syndrome even at higher IC 50 in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, the proportion of cats that received a sedative (butorphanol or buprenorphine) in each of the 3 groups was not statistically different, and a recent report suggested that sedatives do not significantly alter echocardiographic measurements in cats 38. Also, furosemide may alter right heart chamber dimensions, because hydration status has been shown to produce changes in normal cats that may lead to an erroneous diagnosis of HCM 39.…”
Section: Discussionmentioning
confidence: 95%
“…Os escassos estudos existentes avaliaram o uso da cetamina associada a outros agentes anestésicos (opioides, alfa-2-agonistas e tranquilizantes) procurando determinar alterações cardiovasculares e/ou a facilidade de manipulação do paciente, objetivando mínima influência nos resultados de exames complementares, como, por exemplo, a ecocardiografia (Cilli et al, 2010;Slack et al, 2011;Ward et al, 2012).…”
Section: Resultsunclassified
“…Esses resultados corroboram os encontrados por Ward et al (2012), que utilizaram dois protocolos de sedação: acepromazina e butorfanol, associados ou não à cetamina, para a realização de ecocardiograma em gatos e não identificaram alterações ecocardiográficas importantes em grande parte dos parâmetro avaliados.…”
Section: Resultsunclassified